2020
DOI: 10.1097/md.0000000000022157
|View full text |Cite
|
Sign up to set email alerts
|

Late outcomes of endovascular aortic stent graft therapy in patients with chronic kidney disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our team previously demonstrated that in patients undergoing endovascular aortic stent graft therapy, CKD was an independent predictor of higher rates of in-hospital death, postoperative complications, and all-cause death. 27 Furthermore, patients on dialysis had the poorest outcomes. 27 A recent study of open surgical repair of INAA found similar results, with CKD independently associated with both in-hospital and 90-day deaths.…”
Section: Predictors Of Poor Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our team previously demonstrated that in patients undergoing endovascular aortic stent graft therapy, CKD was an independent predictor of higher rates of in-hospital death, postoperative complications, and all-cause death. 27 Furthermore, patients on dialysis had the poorest outcomes. 27 A recent study of open surgical repair of INAA found similar results, with CKD independently associated with both in-hospital and 90-day deaths.…”
Section: Predictors Of Poor Outcomesmentioning
confidence: 99%
“…27 Furthermore, patients on dialysis had the poorest outcomes. 27 A recent study of open surgical repair of INAA found similar results, with CKD independently associated with both in-hospital and 90-day deaths. 28 Our results further highlighted the significant contribution of renal impairment to the death of patients with INAA.…”
Section: Predictors Of Poor Outcomesmentioning
confidence: 99%